2022
DOI: 10.31219/osf.io/xaz78
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hypervigilance: An Understudied Mediator of the Longitudinal Relationship Between Stigma and Internalizing Psychopathology Among Sexual Minority Young Adults

Abstract: Hypervigilance is often theoretically invoked as a psychological mechanism linking stigma to sexual minority young adults’ elevated risk for internalizing psychopathology. Yet, within sexual minority mental health research, hypervigilance is rarely explicitly assessed but instead commonly conflated with putatively related constructs, such as sexual orientation-related rejection sensitivity and rumination. This lack of measurement consistency and construct clarity has stymied the empirical study of hypervigilan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Interestingly, the current study also found that negative expectations played a larger role in the associations of identity-specific IPV with anxiety and PTSD than in those with depression. This may reflect an underlying hypervigilance that has been shown to be characteristic of both negative expectations for future events (Hendricks & Testa, 2012; Hollinsaid et al, 2022) and anxiety- and trauma-related disorders (American Psychiatric Association, 2022; Grillon, 2008; Grupe & Nitschke, 2013; Riggle et al, 2021). The possible role of hypervigilance in these relationships should be explored in future research.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the current study also found that negative expectations played a larger role in the associations of identity-specific IPV with anxiety and PTSD than in those with depression. This may reflect an underlying hypervigilance that has been shown to be characteristic of both negative expectations for future events (Hendricks & Testa, 2012; Hollinsaid et al, 2022) and anxiety- and trauma-related disorders (American Psychiatric Association, 2022; Grillon, 2008; Grupe & Nitschke, 2013; Riggle et al, 2021). The possible role of hypervigilance in these relationships should be explored in future research.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that these factors may partially mediate this observed relationship. Additional psychosocial mechanisms-including hypervigilance (94), emotion regulation (95), concealment (96), and social isolation (97), which collectively influence allostatic processes by recalibrating stress responses that can contribute to AL over time (85)-warrant investigation in future work.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Structural stigma leads to both chronic distal minority stressors (e.g., victimization, discrimination, lack of social safety) and subsequent minority stress reactions, or internal processes within the SM person (Feldman & Meyer, 2007; Meyer, 1995). These reactions include internalized stigma (i.e., negative attitudes towards, and/or nonacceptance of, one's own SM identity), sexual orientation concealment, and SM‐related hypervigilance (chronic anxious expectations of rejection due to sexual orientation; Hollinsaid et al, 2023; Pachankis et al, 2023). Minority stressors increase vulnerability to ED behaviors through resultant negative emotions and maladaptive coping (Calzo et al, 2020; Gordon et al, 2016; Gordon et al, 2019; Katz‐Wise et al, 2015).…”
Section: Introductionmentioning
confidence: 99%